Erythromycin versus neomycin in the treatment of hepatic encephalopathy in cirrhosis: A randomized double-blind study - Romeiro, Fernando Gomes [UNESP]; da Silva Yamashiro, Fabio [UNESP]; Américo, Madileine Francely; Corá, Luciana Aparecida; Silva, Giovanni Faria [UNESP]; Miranda, JoséRicardodeArruda [UNESP]; Caramori, Carlos Antonio [UNESP] (Springer Nature, 2013)
Background: Hepatic encephalopathy (HE) is a severe complication in patients with hepatic cirrhosis, which causes numerous hospital admissions and deaths. Antibiotics are the best options in HE treatment, but head-to-head comparisons between these drugs are scarce. Erythromycin combines the antimicrobial effect and prokinetic properties in the same drug, but it has never been used in HE treatment. Our aim was to evaluate the efficacy of erythromycin as an HE treatment.Methods: We achieved a randomized controlled trial of adult patients with HE and hepatic cirrhosis admitted in our hospital. After randomization, the subjects received either erythromycin 250 mg or neomycin 1 g orally QID until hospital discharge or prescription of another antibiotic. All subjects were blindly evaluated every day towards quantifying clinical, neuropsychometric, hepatic and renal exams. Statistical analysis was employed to compare the groups and correlate the variables with hospitalization duration.Results: 30 patients were evaluated (15 treated with each drug). At hospital admission, the groups were homogeneous, but the erythromycin group subjects achieved a shorter hospitalization stay (p = 0.032) and a more expressive reduction in alanine aminotranspherase levels (p = 0.026). Hospitalization duration was positively correlated with C reactive protein levels measured previous to (p = 0.015) and after treatment (p = 0.01).Conclusions: In the sample evaluated erythromycin was associated with significant reductions in hospital stay and in alanine aminotranspherase values. Hospitalization time was positive correlated with C reactive protein levels measured before and after the treatments. © 2013 Romeiro et al.; licensee BioMed Central Ltd.
Keywords: Erythromycin; Hepatic encephalopathy; Liver cirrhosis; Neomycin; alanine aminotransferase; antibiotic agent; C reactive protein; erythromycin; erythromycin estolate; neomycin; adult; alanine aminotransferase blood level; antibiotic therapy; clinical article; clinical evaluation; clinical examination; controlled study; double blind procedure; drug efficacy; female; hepatic encephalopathy; hospital admission; hospital discharge; hospitalization; human; kidney examination; length of stay; liver cirrhosis; liver examination; male; neuropsychological test; prescription; protein blood level; quantitative analysis; randomization; randomized controlled trial; treatment response; Administration, Oral; Adult; Aged; Alanine Transaminase; Anti-Bacterial Agents; C-Reactive Protein; Dose-Response Relationship, Drug; Double-Blind Method; Female; Hepatic Encephalopathy; Humans; Length of Stay; Liver Cirrhosis; Male; Middle Aged; Treatment Outcome